2013
DOI: 10.1093/heapro/dat047
|View full text |Cite
|
Sign up to set email alerts
|

Do health-promoting schools improve nutrition in China?

Abstract: To demonstrate the effectiveness of health-promoting school framework to promoting healthy eating behaviours and nutrition knowledge among Chinese middle school students, their parents and school staff. Three schools were randomly selected from 15 rural middle schools, then were randomly assigned to either (i) school using HPS framework (HPS school), (ii) school with improved health education only (HE school) or (iii) school received no intervention (control school). Nutrition knowledge and eating behaviours w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 24 publications
2
30
0
Order By: Relevance
“…The results showed that some of adolescents' knowledge, attitudes and behaviour in relation to nutrition improved significantly after this 6-month nutrition education, which demonstrates that this nutrition education program is effective to promote adolescents' nutrition in rural areas of China. These findings are consistent with the results of previous studies, which showed that school-based nutrition interventions can play a major role in dietary change among adolescents because the amount of time young people spend at school and the large percentage of food they consume there, parental influence on diet decreases and the food provided in schools and the influence of peers become more important [16][17][18]. Also, nutrition education has been widely integrated into the formal curriculum for many years.…”
Section: Discussionsupporting
confidence: 91%
“…The results showed that some of adolescents' knowledge, attitudes and behaviour in relation to nutrition improved significantly after this 6-month nutrition education, which demonstrates that this nutrition education program is effective to promote adolescents' nutrition in rural areas of China. These findings are consistent with the results of previous studies, which showed that school-based nutrition interventions can play a major role in dietary change among adolescents because the amount of time young people spend at school and the large percentage of food they consume there, parental influence on diet decreases and the food provided in schools and the influence of peers become more important [16][17][18]. Also, nutrition education has been widely integrated into the formal curriculum for many years.…”
Section: Discussionsupporting
confidence: 91%
“…The target behaviours in the reviewed studies included increasing fruit and/or vegetable consumption (n = 19); improving snacking behaviours (n = 8) (this included both decreasing the intake of energy‐dense nutrient‐poor snacks) and increasing healthy snacks like fruits and vegetables; decreasing sugar‐sweetened beverage (SSB) intake (n = 8); encouragement to eat meals on a regular basis (n = 4); improving general eating behaviours (eg, increase daily nutritional recommended intake of carbohydrates, fibre minerals, protein, and vitamins, n = 5), and reducing daily fat and sugar intake (n = 3) . A number of studies (n = 13) targeted more than one dietary behaviour in their intervention (eg, increasing fruit and vegetable consumption, decreasing SSB and unhealthy snacks consumption) …”
Section: Resultsmentioning
confidence: 99%
“…In terms of eating behaviour assessments, behavioural measures included food frequency questionnaires (FFQ) (n = 24), food diaries over periods of time ranging from 24 hours to 7 days (n = 3; including one online), dietary interviews including general structured interviews on daily dietary consumption (n = 2), a paired food questionnaire (one healthy and one unhealthy option; n = 2), and a “true or false” food statement questionnaire (would you eat a foodstuff, “true or false”; n = 1). All of the reviewed studies had a “before and after” measurement of dietary behaviour, and 14 studies included a longer‐term follow‐up assessment (ranging from 6 weeks to 4 years), whilst two studies also included a measure mid‐intervention …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations